Mechanical and thermal properties of Montmorillonite filled date palm leaf fiber reinforced recycled polyethylene terephthalate nanocomposites - Dehghani, Alireza (2012)
Date palm leaf fiber (DPLF) reinforced recycled poly(ethylene terephthalate) (PETr) nanocomposites containing montmorillonite (MMT) were prepared by melt extrusion using a counter rotating twin-screw extruder followed by injection molding. The influence of the DPLF and MMT along with 10 phr of SEBS-g-MA as compatibilizer on the mechanical and thermal properties of the PETr matrix was evaluated separately, through their individual contributions. The effect of various DPLF additions at from 5 to 15 wt% and the incorporation of 1, 3 and 5 phr of MMT were investigated. Scanning electron microscopy (SEM) was used to investigate the phase morphology and study the adhesion between the matrix and DPLF fibers while the dynamic mechanical properties were studied via dynamic mechanical analysis (DMA). The thermal properties were determined using thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The results showed that blending SEBS-g-MA with PETr matrix significantly increased the toughness at the expense of stiffness of the blend. The incorporation of DPLF resulted in enhancements in tensile and flexural strength of the composites. However, a decrease in the Young’s and flexural moduli was recorded. Fiber additions also improved the impact strength of the composites and an increase in the area under the stress-strain curve was observed. SEM revealed a strong interfacial bonding between the matrix and fibers, and a homogenous one phase system, indicating strong interactions between the PETr matrix and SEBSg- MA. The DSC results showed that the crystallization process was enhanced through the incorporation of DPLF fibers, and a higher degree of crystallinity was observed as compared to PETr. However, TGAshowed that, fiber addition lowered the thermal stability of the composites. The incorporation of MMT resulted in a significant increase in the stiffness of the nanocomposites and 58% increment was observed in the flexural modulus was recorded. The addition of nanoparticles also increased the degree of crystallinity for 1 and 3 phr of nanoclay addition. Thermal stability enhancements were observed for all nanocomposite formulations. The results pointed to a successful development of a hybrid nancomposite from recycled PET and natural fiber with the potentialof various outdoor applications.